1995
DOI: 10.1523/jneurosci.15-10-06757.1995
|View full text |Cite
|
Sign up to set email alerts
|

TOAD-64, a gene expressed early in neuronal differentiation in the rat, is related to unc-33, a C. elegans gene involved in axon outgrowth

Abstract: Using two-dimensional gel electrophoresis we previously identified membrane-associated proteins that are upregulated over the course of neurogenesis. One of these, TOAD-64 (Turned On After Division, 64 kDa), is expressed immediately after neuronal birth and is dramatically downregulated in the adult. The gene encoding TOAD-64 has now been cloned, and its sequence shows homology to the unc-33 gene from C. elegans, mutations in which lead to aberrations in axon outgrowth. Northern and in situ hybridization show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
189
0
7

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(206 citation statements)
references
References 24 publications
10
189
0
7
Order By: Relevance
“…The majority of GAD 65 Ļ© -BrdU Ļ© cells had the morphological characteristics (irregular/triangular cells bodies) of GABAergic interneurons located in the subgranule zone. Subsequently, we stained these sections with TUC-4, which labels immature neurons (Minturn et al, 1995). We found that the GAD 65 Ļ© -BrdU Ļ© cells were colabeled by TUC-4 (GAD 65 Ļ© -BrdU Ļ© -TUC-4 Ļ© ) (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…The majority of GAD 65 Ļ© -BrdU Ļ© cells had the morphological characteristics (irregular/triangular cells bodies) of GABAergic interneurons located in the subgranule zone. Subsequently, we stained these sections with TUC-4, which labels immature neurons (Minturn et al, 1995). We found that the GAD 65 Ļ© -BrdU Ļ© cells were colabeled by TUC-4 (GAD 65 Ļ© -BrdU Ļ© -TUC-4 Ļ© ) (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Whole-cell calcium currents were isolated using the following solutions: external (bath) medium (in mM): NaCl 128, KCl 5, MgCl 2 1, BaCl 2 10, D-glucose 10, HEPES-Na 10, and tetraethylammonium-Cl 10; with an osmolarity of 300 mosm/l and pH 7.3; patch electrode intracellular solution: CsCl 2 110, EGTA 10, MgSO 4 1, HEPES(Cs) 25, ATP 2, and GTP 0.2; osmolarity 305 mosm/l, pH 7.4. Tetrodotoxin (1 lM; Alomone Laboratories) was added in the bath solution to block Na + and Ltype Ca 2+ channels.…”
Section: Electrophysiologymentioning
confidence: 99%
“…Initially identified in chick sensory neurons as a protein responsible for growth cone retraction in response to negative guidance signals in the semaphorin 3A (Sema3A) pathway [1], CRMP-2 analogues were subsequently identified in Caenorhabditis elegans (uncoordinated protein-33 (Unc-33)) [2], in rodents ((named turned on after development 64 (TOAD-64)) in rats and Unc-33 like phosphoprotein (Ulip) in mice) [3][4][5], in humans (HUlip) [6,7] and in Drosophila Melanogaster [8]. Together with its established roles in neurite growth and retraction and kinesin-dependent axonal transport, mapping the CRMP-2 interactome has revealed previously unappreciated functions including affecting microtubule dynamics, protein endocytosis and vesicle recycling, as well as synaptic assembly (see reviews by Hensley [9] and Strittmatter [10]).…”
Section: Introductionmentioning
confidence: 99%
“…Two additional members of this family, TUC-1 and TUC-3, were identified by homology to TUC-2 and TUC-4 (Wang and Strittmatter, 1996). Indirect evidence for a role of the TUCs in axon outgrowth comes from the observation that TUC-4 is expressed in growth cones and is upregulated in motor neurons during axonal regeneration after sciatic nerve lesion (Minturn et al, 1995a). A role for TUC-2 in axon guidance is suggested by the observation that antibodies to CRMP-62 (TUC-2) can inhibit semaphorin-3A-mediated growth cone collapse (Goshima et al, 1995).…”
Section: Introductionmentioning
confidence: 99%